SOSIALISASI MODEL BISNIS HIJAU DALAM MENDORONG TRANSFORMASI EKONOMI HIJAU PADA IBU RUMAH TANGGA DIDESA SUMUR DALAM PROBOLINGGO - Pradani, Rizki Febri Eka; Rusmawati, Rusmawati; Izzah, Nailul; Kulsum, Ummi; Pramita, Riska Dwi; Novianti, Nuraini Ike (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM Azramedia Indonesia, 2024)
Green business has become a significant issue due to the environmental crisis and increasing consumption that lacks sustainability awareness. Implementing green business for housewives in Sumur Dalam Village, most of whom are unemployed, is crucial to promote a green economy and enhance creativity in producing marketable products. This community service activity aims to increase understanding of green business models among housewives in Sumur Dalam Village, enabling them to build businesses that contribute to the environment and improve family income. The partners in this activity are 20-30 housewives aged 20-35 years who are unemployed, encouraging entrepreneurship. The implementation method consists of preparation, execution, and evaluation. The expected result of this activity is to enhance the creativity and understanding of housewives regarding green business.